Resilient Traditions and Changing Spaces: Vernacular Architecture and Livelihood Shifts in Assam’s Handloom and Handicraft Settlements - Bhattacharya, Anashuiya; Mishra, Priyanka; Jena, Damodar; Thakur, Rakesh Ranjan; Neelannavar, Vishwanath; Nayak, Bandana (Indian Journal of Information Sources and Services, 2025)
The handloom and bell-metal craft sectors are integral to Assam’s socio-economic fabric, reflecting its rich cultural heritage and economic identity, particularly in the traditional settlements of Sualkuchi and Sarthebari. However, these communities are undergoing a rapid transformation due to the growing influence of modernization, changing lifestyles, and shifting socio-economic conditions. This paper examines the transformations in vernacular architecture and its intrinsic connection to local artisanal livelihoods. Using a mixed-method approach comprising field surveys, interviews, focus group discussions, and spatial mapping, the research documents the production techniques, settlement patterns, and built forms in these craft-based communities. The study examines the transition from traditional Assam-type dwellings to reinforced concrete (RCC) structures, investigating how these changes impact spatial functionality, sustainability, and cultural continuity. Findings suggest that while contemporary materials improve structural durability, they often compromise climatic responsiveness and disrupt the historic integration of living and working spaces. This disruption threatens the long-standing artisanal traditions that are deeply tied to the built environment. The paper highlights the urgent need for sustainable, culturally rooted design strategies and recommends hybrid construction approaches, community participation in planning, and integration of traditional knowledge into rural development frameworks. These interventions are critical for reconciling heritage preservation with the demands of modern living in Assam’s artisanal settlements.